2017
DOI: 10.1186/s12913-017-2797-8
|View full text |Cite
|
Sign up to set email alerts
|

Academic detailers’ and general practitioners’ views and experiences of their academic detailing visits to improve the quality of analgesic use: process evaluation alongside a pragmatic cluster randomized controlled trial

Abstract: BackgroundContinuous medical education strategies, including academic detailing (AD), have mixed effects on the quality of prescribing in general practice. Alongside a cluster-randomized controlled trial (cRCT) to assess the effectiveness of AD visits (on appropriate prescribing of analgesics for chronic pain in osteoarthritis) by Farmaka, an independent drug information center, we performed a process evaluation to identify possible barriers and success factors to improve these AD visits, both from the perspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(51 citation statements)
references
References 21 publications
0
50
1
Order By: Relevance
“…Others have also shown that users of AD highly appreciate its educational value and, due to their positive experience with AD, tend to view information from other sources and other forms of continuing medical education more critically 29. In a study from Belgium, the GPs concluded that the visits were a credible and interesting way of receiving continuing medical education and that they both enhanced their knowledge and increased their reflections on their own prescribing behaviour 30. That the service is free for the GP and that the GP does not have to leave the office eliminates the need for travel and minimizes any loss of income for the GP.…”
Section: Discussionmentioning
confidence: 99%
“…Others have also shown that users of AD highly appreciate its educational value and, due to their positive experience with AD, tend to view information from other sources and other forms of continuing medical education more critically 29. In a study from Belgium, the GPs concluded that the visits were a credible and interesting way of receiving continuing medical education and that they both enhanced their knowledge and increased their reflections on their own prescribing behaviour 30. That the service is free for the GP and that the GP does not have to leave the office eliminates the need for travel and minimizes any loss of income for the GP.…”
Section: Discussionmentioning
confidence: 99%
“…A central component of the practice-team intervention was an outreach visit by experienced outreach visitors (OVs) who presented general information on antibiotic prescribing and the CHANGE-3 project. Outreach visits are considered to be a credible instrument in continuous medical education [ 20 ] and might be chosen for changes which are considered to be difficult to achieve [ 21 ]. They can improve the care delivered to patients and provide small to moderate changes in prescribing patterns [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…A central component of the practice-team intervention was an outreach visit by experienced outreach visitors (OVs) who presented general information on antibiotic prescribing and the CHANGE-3 project. Outreach visits are considered to be a credible instrument in continuous medical education [18] and might be chosen for changes which are considered to be di cult to achieve [19]. They can improve the care delivered to patients and provide small to moderate changes in prescribing patterns [20].…”
Section: Implementation Programmentioning
confidence: 99%